Janusza Korczaka językowa gra z odbiorcą w racje i emocje – spotkanie dwóch perspektyw - Małgorzata Dagiel (Problemy Wczesnej Edukacji)
Janusz Korczak’s literary writing can be perceived as an endeavour to change the world, to make the world fair and marked by greater solidarity. The reading of his texts draws attention of the recipient to the ways in which he characterises children and calls for the necessity of treating them rightly by adults. The author of the article focuses on the persuasiveness of narration, understood as a specific game played with the recipient, and the linguistic features used by Korczak in his literary works. The aim of the article is to show the linguistic features employed by Korczak in presenting theses regarding the situation of children and expressing his beliefs about the protection of children’s rights. The author analysed Korczak’s literary work entitled When I am Little Again. Stylistically diverse narration is subordinated to one goal – convincement of the recipient to the narrator’s arguments. Considered as a whole, the article is an attempt to combine a pedagogical perspective with the poetics of reception.